Pendampingan Penulisan Artikel Ilmiah di SMP Negeri 4 Rambutan - Tresiana Sari Diah Utami; Katarina Retno Triwidayati (CV. Creative Tugu Pena, 2021)
The article was to give assistance in training writing article at SMP Negeri 4 Rambutan. This activity was based on the needs of educators at SMP Negeri 4 Rambutan, Banyuasin to publish their writings about their experiences and knowledge of experiencing education. The method used a method of discussion and assignment for students. The first meeting, participants and teams met through a zoom meeting, through two or three meetings participants discussed via WA Group, and the last meeting was held through zoom meeting again. The participants were asked to write down three tasks in this assistance. The first task is to determine the writing outline and the topic, the second task is to improve the writing outline and opening paragraph, and the third task is to ask participants to write an article of at least 700 words. The results showed that all participants were able to write articles of at least 700 words on various topics. The two teachers who wrote their respective articles succeeded in publishing the articles they wrote in print media, online media based on the open journal system. The output in this activity is that educators are able to write articles. After the activity, it is hoped that the educators will understand the techniques, models, and stages in writing articles with project results in the form of articles. Keywords: Training Writing Article, Assistance Writing Article, Publication Article